The African L3e5a haplogroup in the Icelandic population - Ragnheiður Diljá Ásmundsdóttir 1994- (2017)
The genetic composition of Icelanders has been widely researched. For the last couple of decades deCODE genetics in Iceland has collected DNA samples from more than half the Icelandic population. Studies of mitochondrial DNA from the genetic database as well as data from the genealogical database have revealed that the Icelandic population is largely descendant from Scandinavia and the British Isles. However, a small proportion of the Icelandic population are carriers of rare groups of mtDNA. One of those groups is L3e5a that is usually found in North and Central Africa. The Icelandic L3e5a therefore possibly has African origins. The objective of this study is to determine when carriers of this haplogroup arrived in Iceland. Two hypotheses exist. The first hypothesis is that the L3e5a haplogroup arrived around 870 AD at the time of the settlement in Iceland. The second hypothesis is that the haplogroup arrived later and possibly with those who returned from the Turkish abductions in 1627. In the deCODE genetic database 74 individuals were found carrying the L3e5a haplogroup and all individuals could be traced to five matrilineal ancestors born between 1630 and 1748. Consensus sequences were made for the five ancestors and compared with 34 mtDNA sequences from literature. One sequence, from Hungary, had similarities to the Icelandic ones but the origin of that sequence is unknown. The frequency of the haplogroup in the Icelandic population was compared to other European populations, as well as few from Africa, to see whether the Icelandic frequency differed. The haplogroup has not been found in Scandinavia or the British Isles. Predicted frequencies for these areas are similar to Iceland. This suggests that the haplogroup may be found there in small numbers, and has not been found due to small sample size. In conclusion it is likely that the L3e5a haplgroup arrived with the settlement. Erfðamengi Íslendinga hefur verið mikið rannsakað. Á seinustu tveimur áratugum hefur Íslensk erfðagreining safnað lífsýnum úr ...